Traditional Tibetan Medicine Twenty-Five Wei’er Tea Pills Ameliorate Rheumatoid Arthritis Based on Chemical Crosstalk Between Gut Microbiota and the Host - Li, Zixuan; Nie, Lijuan; Li, Yong; Yang, Lu; Jin, Lulu; Du, Baozhong; Yang, Juan; Zhang, Xulin; Cui, Huantian; Luobu, Ouzhu (Frontiers in Pharmacology, 2022)
Twenty-Five Wei'er Tea Pills (TFP), a traditional Tibetan medicine, has shown promising therapeutic effect on Rheumatoid arthritis (RA) patients and exhibited satisfactory safety. However, few pharmacological research has been reported regarding this medicine. Gut microbiota have been proved to play important roles in RA pathogenesis. Thus, this study aimed to revealed potential mechanism of TFP on RA based on chemical crosstalk between gut microbiota and host. 16S rRNA sequencing combined with untargeted metabolomics were conducted on collagen-induced arthritis (CIA) rats. CIA model rats treated with TFP showed significant improvement in weight gain, pathological phenomena in joints, as well as decreased serum level of TNF-α, IL-6 and increased level of IL-4, IL-10. Significant dysfunction in gut microbiota community and alteration in serum metabolites were observed in CIA model rats, which were restored by TFP treatment. Coherence analysis indicated that TFP modulated the pathways of histidine metabolism, phenylalanine metabolism, alanine, aspartate, glutamate metabolism, amino sugar and nucleotide sugar metabolism by the abundances of Lactobacillus, Bacteroides, Prevotellaceae_UCG-001 and Christensenellaceae_R-7_group in the gut microflora. The corresponding metabolites involved L-histidine, histamine, phenylethylamine, asparagine, L-aspartic acid, D-fructose 1-phosphate, D-Mannose 6-phosphate, D-Glucose 6-phosphate, Glucose 1-phosphate. In conclusion, this study revealed the ameliorative effects and potential mechanism of TFP on RA based on chemical crosstalk between gut microbiota and host, which also enriched understandings about pathogeny of RA.